Dynamic Biomaterials: Cyclic Stiffness Modulation of Cell‐Laden Protein–Polymer Hydrogels in Response to User‐Specified Stimuli Including Light (Adv. Biosys. 12/2018). Issue 12 (7th December 2018) - Liu, Luman; Shadish, Jared A.; Arakawa, Christopher K.; Shi, Kevin; Davis, Jennifer; DeForest, Cole A.
Abstract : In article number1800240, Cole A. DeForest and co‐workers demonstrate that hydrogel biomaterials crosslinked with stimuli‐responsive fusion proteins can undergo fully reversible stiffening upon exposure to user‐specified environmental cues. Gels built upon optogenetic proteins LOV2 and Jα soften near‐instantaneously under blue light, enabling spatiotemporal control of hydrogel compliance in the presence of living cells.